Concept of A Low-Cost Hybrid Car - Dvadnenko, Vladimir; Arhun, Shchasiana; Myhal, Vasiliy; Pushkar, Oleh (International Journal of Integrated Engineering, 2022)
Fuel economy and emissions reduction are the vital tasks, which are currently being solved by dismissing cars with only internal combustion engines to the benefit of electric and hybrid electric vehicles (HEV). HEVs have a significant advantage over electric vehicles, namely a bigger drive range and independence from the charging stations at hand. However, high cost and big weight of HEVs discourage their wider use. To minimize the cost and weight of HEV, the algorithm of its power plant operation is changed. This paper presents a method for calculating the electric drive mode of a hybrid vehicle in accordance with the proposed algorithm for the power plant operation. The results of calculation of the main characteristics are presented and analyzed. The experimental studies were carried out with the hybrid vehicle developed on the base on the Lanos pickup vehicle. The research results showed good agreement between the experimental and the calculated results. The proposed technical solution is presented as practical and effective. The results of this work can be used in the automotive industry. The development helps to reduce the cost and weight of hybrid vehicles, maintaining their operational characteristics and good economic and environmental indicators.